THE ANALYSIS OF COMPARISON OF PSYCHOANALYSIS FREUD AND LACAN, MARX’ COMMODITY AND BOURDIEU’S DISTINCTION - Subanti, Gregorius (Prologue: Journal on Language and Literature, 2026)
This paper aims at analyzing the theories of Psychoanalysis, Marx’s Commodity and Bourdieu’s Distinction. This content analysis utilizes the text of Freud, Lacan, Marx and Bourdieu. Freud and Lacan flourish the theoretical worlds under the term of psychoanalysis. Each shows the different aspects of identifying human consciousness and unconsciousness. Freud, a neurosis, roots his theory of ego, id and superego from his dealing with his patients using dream works as his point of analytical which highlights the oral, anal and phallic stage of mental development of human beings. This study finds out that Lacan deconstructs Freud theory using linguistic aspect which theorizes the metaphor and metonymy use of an individual to the unconsciousness. Marx focuses on commodity exchange and fights of classes in social economy perspective which is more material perspective. Bourdieu with his term “distinction” views that an individual taste is shaped by educational, social and family background. Freud and Lacan focus more on psychology stream. On contrast, Marx and Bourdieu analyze the sociological appearance. After all, society is a group of individuals with heterogeneous backgrounds tied up by an ideological concept. In the long run, an individual identifies himself from the group that he should follow or leave.